1982
DOI: 10.1111/j.2042-3306.1982.tb02446.x
|View full text |Cite
|
Sign up to set email alerts
|

Types of Pseudomonas aeruginosa isolated from horses

Abstract: Summary Pseudomonas aeruginosa isolates from equine clinical material were categorised according to their serotype and phage type. Epidemiological evidence showed that serotypes 02a, 03,04,06, 09 and 010 were the cause of genital and non‐genital infections; somatic type 03 accounted for 50 per cent of isolates. The laboratory tests used were of no value in predicting whether or not a particular isolate was likely to be a venereal pathogen, but all the serotypes encountered had the potential to be pathogenic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Also the variability in incidence of haemolytic Escherichia coli strains (unambiguously associated with reproductive disorders in females) in comparison with non-haemolytic strains, reported in studies by Barrelet (1995), Albihn et al (2003), Frontoso et al (2008) as well as in our study indicate that both types of E. coli strains are important pathogens or potential pathogens populating the reproductive apparatus of mares after parturition. In agreement with other studies (Brown et al 1979;Atherton and Pitt 1982;Frontoso et al 2008) our results showed that Klebsiella spp. and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 83%
“…Also the variability in incidence of haemolytic Escherichia coli strains (unambiguously associated with reproductive disorders in females) in comparison with non-haemolytic strains, reported in studies by Barrelet (1995), Albihn et al (2003), Frontoso et al (2008) as well as in our study indicate that both types of E. coli strains are important pathogens or potential pathogens populating the reproductive apparatus of mares after parturition. In agreement with other studies (Brown et al 1979;Atherton and Pitt 1982;Frontoso et al 2008) our results showed that Klebsiella spp. and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 83%
“…With such an amount of development of methods to aid in the characterisation of P. aeruginosa , it is surprising that similar reports, applying these highly discriminatory molecular methods to collections of P. aeruginosain horses, are absent from the literature. The description of previous typing studies on equine P. aeruginosa is limited to the relatively old report by Atherton and Pitt [ 1 ] from 1982, who employed phenotypic serotyping and phage-typing. This study demonstrated that somatic type O3 accounted for 5% of isolates and that all serotypes had the potential to be pathogenic, given favourable culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is ubiquitous in the environment and commonly causes genital tract infections, pneumonia and ulcerative keratitis in horses (Atherton and Pitt 1982;Blanchard et al 1992). From the aggregated data 31.7% and 23.2% of the Pseudomonas isolates were cultured from respiratory system and uterine/endometrial samples respectively.…”
Section: Equine Colitis and Neonatal Sepsis Are The Most Common Clinimentioning
confidence: 99%